Considerations when providing mental health first aid to an LGBTIQ person: a Delphi study. (3rd July 2017) - Bond, K. S.; Jorm, A. F.; Kelly, C. M.; Kitchener, B. A.; Morris, S. L.; Mason, R. J.
ABSTRACT: Objective: A Delphi study was conducted to develop guidelines on considerations when providing sensitive and appropriate mental health first aid to a lesbian, gay, bisexual, transgender, intersex and queer or questioning (LGBTIQ) person. These can be used in conjunction with existing guidelines when assisting a person who might be experiencing a mental health problem or crisis. Methods: A systematic search of websites, books and journal articles was conducted to develop a questionnaire containing items about the knowledge, skills and actions needed for assisting an LGBTIQ person who is experiencing mental health problems. These items were rated over three survey rounds by an expert panel according to whether they should be included in the guidelines. Results: Seventy-five mental health professionals who were part of the LGBTIQ community or who treated people from the LGBTIQ community participated in the study. Of the 209 items that were rated over the 3 rounds, 164 items were endorsed by at least 80% of panel members. These items formed the basis of the guidelines document that outlines what a person needs to consider when providing mental health first aid to an LGBTIQ person with mental health problems. Conclusion: This research highlighted the complexity of supporting an LGBTIQ person with mental health problems, but also provided specific advice on how to address these complexities. It is hoped that these guidelines will increase support, and decrease stigma and discrimination towards LGBTIQ people who are experiencing mental health problems. More specifically, the guidelines will be used to supplement the content of Mental Health First Aid training courses. Abbreviations: LGBTIQ: lesbian, gay, bisexual, transgender, intersex and queer or questioning; MHFA: mental health first aid Abstract :